PENGARUH FAKTOR LOKASI TERHADAP MINAT KUNJUNGAN PUSAT PERBELANJAAN STUDI KASUS TRANSMART MATARAM - Maulana Alfateh Sahbana; Susanti, Febrita; Ridha, Rasyid (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2026)
Site selection is a critical factor in the success of shopping centers, as it influences accessibility, market potential, and consumers’ visitation decisions. This study aims to analyze the effectiveness of the Transmart Mataram location through both spatial and non-spatial approaches, including service area analysis, location–allocation analysis, simple linear regression, and Analytical Hierarchy Process (AHP) weighting. The service area analysis indicates that Transmart has the widest service coverage within a 3 km radius; however, its effectiveness is relatively low because most of the catchment area consists of low-density residential zones. The location–allocation results confirm that the highest demand allocated to Transmart is dominated by sparsely populated areas, resulting in a mismatch between its spatial coverage and actual visitation potential. The regression results show that location factors have a positive and significant effect on visitation interest, with a significance value of 0.000 and an R² of 0.426, indicating that location explains 42.6% of the variation in consumer visitation interest. Meanwhile, the AHP results reveal that accessibility is the most dominant criterion (0.28), followed by parking (0.16) and environmental factors (0.14), while visibility has the least influence. Overall, this study confirms that location effectiveness is not solely determined by the extent of spatial coverage, but also by the quality of accessibility and proximity to population activity centers. These findings provide a basis for strengthening spatial planning strategies and improving supporting facilities to optimize the attractiveness of Transmart Mataram.